Fragmentation of International Law Revisited: Insights, Good Practices, and Lessons to be Learned from the Case Law of the European Court of Human Rights. (30th October 2015) - RACHOVITSA, ADAMANTIA
Abstract: This article discusses the contribution of the European Court of Human Rights to mitigating difficulties arising from the fragmentation of international law. It argues that the Court's case law provides insights and good practices to be followed. First, the article furnishes evidence that the Court has developed an autonomous and distinct interpretative principle to construe the European Convention on Human Rights by taking other norms of international law into account. Second, it offers a blueprint of the methodology that the Court employs when engaging with external norms in the interpretation process. It analyses the Court's approach to subtle contextual differences between similar or identical international norms and its position towards the requirements of Article 31(3)(c) of the Vienna Convention on the Law of Treaties (VCLT). It concludes that international courts are developing innovative interpretative practices, which may not be strictly based on the letter of the VCLT.